The management of minor traumatic brain injury. Issue 2 (March 1998) - Hutchinson, P J; Kirkpatrick, P J; Addison, J; Jackson, S; Pickard, J D
Abstract : Minor traumatic brain injury accounts for the majority of the one million head trauma attendances at A&E departments in the United Kingdom. Guidelines have been established listing criteria for skull films, admission to hospital, computed tomography, and neurosurgical consultation. These are currently undergoing revision and were the subject of a satellite symposium to the J Douglas Miller memorial meeting held in October 1996 in Edinburgh. In the East Anglia Region the current guidelines have been issued as memo-cards for A&E officers. The aim of admission is to observe for deterioration, predominantly caused by intracranial haematomas. The indicators for the development of such lesions are an impaired level of consciousness and presence of a skull fracture. Such patients should therefore undergo regular and frequent neurological observations, and be admitted for at least 12 hours. Following discharge, routine follow up should be considered to identify and treat patients with postconcussion symptoms and signs. The possible way forward for the management of these patients is adopting a greater emphasis on preventative aspects, and establishing, implementing, and auditing evidence based guidelines. Improved teaching in the form of formal induction seminars and computerised teaching aids is required, and a better understanding of the aetiology and treatment of the postconcussion syndrome.